1996
DOI: 10.1007/bf03162235
|View full text |Cite
|
Sign up to set email alerts
|

Line-shifting method in electron spin echo envelope modulation (ESEEM) studies

Abstract: A novel line-shifting method, which is ealled mixing-frequency electron spin echo envelope modulation (MIF-ESEEM) spectroseopy, is introduced and analysed. Ir is shown that the spectral resolution is enhanced, and thus the overlapping is removed with this new method. The application of this method to systems with S > 1 and 1 > 1 is also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The purpose of the present article is to justify the previously published 1-D and 2-D formulae [3,5,8,11] by providing a detailed descfiption of how the time~ domain signal is acquired and to show that the parametrization of the time va¡ ables suggested in reŸ 10 is inconsistent with this description. The equivalence of the MIF-ESEEM paramet¡ with that used by Hubrich et al [6] is highlighted and it is shown that MIF-ESEEM represents a natural extension to the special cases of y= 0, _+1.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…The purpose of the present article is to justify the previously published 1-D and 2-D formulae [3,5,8,11] by providing a detailed descfiption of how the time~ domain signal is acquired and to show that the parametrization of the time va¡ ables suggested in reŸ 10 is inconsistent with this description. The equivalence of the MIF-ESEEM paramet¡ with that used by Hubrich et al [6] is highlighted and it is shown that MIF-ESEEM represents a natural extension to the special cases of y= 0, _+1.…”
Section: Introductionmentioning
confidence: 72%
“…In reŸ 6, the above three schemes were combined into four different 2-D correlation experiments. Song et al also published a description of 1-D and 2-D experiments in which t 2 is linearly constrained to tt by a factor 7" that is not restricted to the above cases of 0 and +_ 1, providing examples for both homogeneous [3,5,8] and inhomogeneous [9] broadening. They referred to these experiments as mixing-frequency electron spin-echo envelope modulation (MIF-ESEEM).…”
Section: Introductionmentioning
confidence: 99%